Like lions : a novel - Panowich, Brian (Minotaur Books, 2019)
"Clayton Burroughs is a small-town Georgia sheriff, a new father, and, improbably, the heir apparent of Bull Mountain's most notorious criminal family. As he tries to juggle fatherhood, his job and his recovery from being shot in the confrontation that killed his two criminally-inclined brothers last year, he's doing all he can just to survive. Yet after years of carefully toeing the line between his life in law enforcement and his family, he finally has to make a choice."--